2013
DOI: 10.1002/cncr.28352
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcomes in women with breast cancer enrolled in a dual‐center, double‐blind, randomized controlled trial assessing the effect of acupuncture in reducing aromatase inhibitor‐induced musculoskeletal symptoms

Abstract: Background Aromatase Inhibitors (AIs) have been associated with decrements in patient-reported outcomes (PROs). Objectives To assess if real acupuncture (RA) compared to sham acupuncture (SA) improves PROs in breast cancer patients taking adjuvant AI. Methods Postmenopausal women with a stage 0-III breast cancer on AI with treatment-associated musculoskeletal symptoms were randomized to 8 weekly RA vs SA in a dual-center randomized controlled trial. National Surgical Adjuvant Breast and Bowel Project (NSAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
92
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(107 citation statements)
references
References 37 publications
2
92
0
11
Order By: Relevance
“…Finally, it is possible that the current study may have employed an inadequate dose of acupuncture which could also have led to an underestimate of the true benefit from active acupuncture. Compared with other cancer studies, treatment provided once every 2 weeks represents a very low frequency, and other studies have reported that more acupuncture sessions are associated with better outcomes [4,5,31]. Given the severity of concurrent CRT toxicity, a higher frequency of acupuncture sessions, for example, three times per week, should be considered in a future trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is possible that the current study may have employed an inadequate dose of acupuncture which could also have led to an underestimate of the true benefit from active acupuncture. Compared with other cancer studies, treatment provided once every 2 weeks represents a very low frequency, and other studies have reported that more acupuncture sessions are associated with better outcomes [4,5,31]. Given the severity of concurrent CRT toxicity, a higher frequency of acupuncture sessions, for example, three times per week, should be considered in a future trial.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is a traditional Chinese medical technique that has been found to reduce symptoms and side effects associated with primary cancer therapy [3][4][5]. More recently, research has begun to evaluate the efficacy and underlying mechanisms through which acupuncture may reduce dysphagia, including in HNC patients [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, sham acupuncture may not be truly inert and may have underlying physiological effects, and hence may not be a proper control group. 28,29 To enable us to design a large pragmatic trial, we decided not to use sham acupuncture as control in this study. In contrast to previous Chinese trial in stroke, we used binary outcome as primary outcome (dependency or independency according to BI score) because the systematic review suggested that placebos had no significant effects on objective or binary outcomes in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Non-steroidal AIs include anastrozole, vorozole, and letrozole [12,13] . Previous studies have demonstrated that AIs provide an increased survival benefit compared with other therapies and have acceptable toxicity profiles with decreased virginal bleeding and thromboembolism and increased rash, diarrhea and vomiting [14,15] . As AIs sometimes have more severe bone, brain and heart side effects, research for alternative compounds is necessary [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that AIs provide an increased survival benefit compared with other therapies and have acceptable toxicity profiles with decreased virginal bleeding and thromboembolism and increased rash, diarrhea and vomiting [14,15] . As AIs sometimes have more severe bone, brain and heart side effects, research for alternative compounds is necessary [15][16][17] .Natural products, extracted from traditional medicines and foods, may be helpful for discovering novel AIs that may selectively target aromatase in the breast and reduce systemic toxicity [18] . Among these compounds, flavonoids [19] are the most commonly investigated agents due to their prominent aromatase inhibitory activity and high breast selectivity [18] .…”
mentioning
confidence: 99%